Logistyka zaopatrzenia przedsiębiorstwa produkcyjnego w aspekcie strategii globalnych sieci logistycznych - Witkowski, Krzysztof (The Purchasing in Supply Chain on the Aspect of the Logistics Network Global Strategy, 2005)
In the paper there are presented the problems of purchasing (in supply chain) on aspect of construct the competitive strategy. This article is a part of research, which is considered to the problem of logistical controlling functionality in small and middle enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 292-299